The policy analysis of non transmitted disease integrated post in the regency of Sukoharjo Indonesia - Sri Sugiarsi; Erna Adita Kusumawati (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
This research is aimed at analyzing the implementation of Integrated Development Post of Non-Trasmitted Diseases viewed from idealized policy, targeted group, implementing organization and environment factors. This research was conducted in the villages of Triyagan and Laban. The data was collected through depth interview, observation, and documentation. The data were analyzed using interactive analysis (Miles&Huberman). The findings of the research show that the policy implementation of the integrated development post of non-transmitted diseases has not fully applied the components from the policy component. The condition caused this problem are unideal number and role of the cadres, lack of guidance from the community health center, economic factor. So it can be concluded that the policy implementation of integrated development post of non-transmitted disease is not maximum yet.